Quality of life and cost effectiveness in a randomized trial of patients with colorectal cancer and peritoneal metastases. Issue 7 (July 2018) - Cashin, P.H.; Mahteme, H.; Syk, I.; Frödin, J.E.; Glimelius, B.; Graf, W.
Abstract: Background: The aim was to compare health-related quality-of-life (HRQOL) and cost-effectiveness between cytoreductive surgery with intraperitoneal chemotherapy (CRS + IPC) and systemic chemotherapy for patients with colorectal peritoneal metastases. Methods: Patients included in the Swedish Peritoneal Trial comparing CRS + IPC and systemic chemotherapy completed the EORTC QLQ-C30 and SF-36 questionnaires at baseline, 2, 4, 6, 12, 18, and 24 months. HRQOL at 24 months was the primary endpoint. EORTC sum score, SF-36 physical and mental component scores at 24 months were calculated and compared for each arm and then referenced against general population values. Two quality-adjusted life-year (QALY) indices were applied (EORTC-8D and SF-6D) and an incremental cost-effectiveness ratio (ICER) per QALY gained was calculated. A projected life-time ICER per QALY gained was calculated using predicted survival according to Swedish population statistics. Results: No statistical differences in HRQOL between the arms were noted at 24 months. Descriptively, survivors in the surgery arm had higher summary scores than the general population at 24 months, whereas survivors in the chemotherapy arm had lower scores. The projected life-time QALY benefit was 3.8 QALYs in favor of the surgery arm ( p =0.06) with an ICER per QALY gained at 310, 000 SEK (EORTC-8D) or 362, 000 SEK (SF-6D) corresponding to 26, 700–31, 200 GBP. Conclusion: The HRQOL in patients with colorectal peritoneal metastases undergoing CRS + IPC appear similar to those receiving systemic chemotherapy. Two-year survivors in the CRS + IPC arm have comparable HRQOL to a general population reference. The treatment is cost-effective according to NICE guidelines. Abstract : Synopsis: This study reports the health-related quality-of-life and cost-effectiveness between surgical treatment and systemic chemotherapy treatment in a randomized setting for patients with colorectal cancer and peritoneal metastases. The surgical treatment has good quality-of-life and is cost-effective.